Studi Perbandingan: Penerapan Regulasi Kawasan Tanpa Rokok di Indonesia dengan Singapura Berdasarkan Komponen Sistem Hukum Lawrence M. Friedman - Irna Pramayora; Deppa Ringgi (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The Implementation of Smoke-Free Areas (KTR) is an important effort in tobacco control to protect the public from the dangers of smoking. This research aims to analyze the comparative implementation of KTR regulations between Indonesia and Singapore using Lawrence M. Friedman's legal system approach, which includes components of legal substance, legal structure, and legal culture. The research method employed is normative juridical with a comparative legal approach, using secondary data collected through literature study and analyzed qualitatively. The research results show that in terms of legal substance, KTR regulations in Singapore are more comprehensive and stringent with heavy sanctions, while in Indonesia they remain partial with relatively light sanctions. In the legal structure aspect, Singapore has a more effective system of supervision and law enforcement with technological support and adequate human resources, whereas Indonesia still faces coordination challenges between institutions and limited supervisory personnel. From the legal culture perspective, the level of awareness and compliance of Singaporean society towards KTR regulations is higher compared to Indonesia, which is still influenced by a permissive culture towards smoking behavior.